Superelastic grindstone

The superelastic grindstone with a binder containing rubber latex, partial acetalized PVA, and a graft polymer addresses the issue of wear and compatibility by enhancing abrasion resistance and maintaining adhesion to workpieces, resulting in improved polishing performance and reduced defects.

JP2025062429APending Publication Date: 2025-04-14NIPPON TOKUSHU KENTO
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023171505
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-02
Publication Date
2025-04-14

AI Technical Summary

Technical Problem

Existing superelastic grindstones with rubber latex as a binder suffer from increased wear, compromising their compatibility with complex workpiece shapes and requiring frequent replacements, which leads to uneven polishing and manufacturing defects.

Method used

A superelastic grindstone with a hardened binder containing rubber latex, partial acetalized polyvinyl alcohol (PVA), and a graft polymer, which forms a three-dimensional matrix-like network and includes open pores to enhance wear resistance and adhesion to workpieces.

Benefits of technology

The proposed superelastic grindstone improves abrasion resistance while maintaining its adhesion to workpieces, reducing wear and the likelihood of clogging, and ensuring stable, high-quality polishing of complex surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025062429000001
    Figure 2025062429000001
  • Figure 2025062429000002
    Figure 2025062429000002
Patent Text Reader

Abstract

To provide a superelastic grindstone which can enhance wear resistance while maintaining conformability to a workpiece.SOLUTION: A superelastic grindstone comprises: abrasive grains; and a base holding the abrasive grains. The base is a cured body of a binder containing rubber latex and at least one of a partially acetalized material of polyvinyl alcohol (PVA), and a graft polymer with PVA serving as a main chain. The base is provided with at least one continuous pore, and a porosity when the base is measured using a mercury intrusion technique is 10 to 40 vol.% inclusive.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a superelastic grinding wheel. [Background technology]

[0002] Grindstones that exhibit superelastic properties (superelastic grindstones) due to the use of rubber latex such as natural rubber or synthetic rubber as a binder may be used. Such superelastic grindstones have excellent compatibility with workpieces (hereinafter simply referred to as "workpieces"). Therefore, superelastic grindstones are often used when the polished surface of the workpiece has a complex shape. On the other hand, when rubber latex is used as a binder, the grindstone tends to wear more. From the viewpoint of improving the wear resistance of such grindstones, Patent Document 1 below discloses a grindstone in which abrasive grains and nonwoven fabric are embedded in a resin molded body. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Patent Publication No. 2021-194723 Summary of the Invention [Problem to be solved by the invention]

[0004] The grinding wheel disclosed in the above Patent Document 1 is inferior to the superelastic grinding wheel in terms of conformability to the workpiece.

[0005] An object of one aspect of the present invention is to provide a superelastic grinding wheel that can achieve improved wear resistance while maintaining conformability to a workpiece. [Means for solving the problem]

[0006] One aspect of the present invention provides a superelastic grinding wheel as described in the following items [1] to [7]. Each embodiment is as follows. [1] Abrasive grains and A body for holding the abrasive grains; Equipped with The body is a hardened body of a binder containing rubber latex and at least one of a partially acetalized product of PVA (polyvinyl alcohol) and a graft polymer having PVA as a main chain, The body has at least one continuous pore; The porosity of the main body is 10% by volume or more and 40% by volume or less when measured by mercury intrusion porosimetry. Super elastic grinding wheel. [2] The superelastic grinding wheel according to [1], wherein, when the body is measured by mercury intrusion porosimetry, the median diameter of the continuous pores is 1 μm or more and 10 μm or less, and the maximum diameter of the continuous pores is 200 μm or less. [3] The superelastic grinding wheel described in [1] or [2], wherein in the binder, the content of the rubber latex is 50% by mass or more and 80% by mass or less, the content of the partially acetalized product is 10% by mass or more and 50% by mass or less, and the content of the graft polymer is 0% by mass or more and 20% by mass or less. [4] The superelastic grinding wheel according to any one of [1] to [3], wherein the rubber latex contains at least one of natural rubber latex, styrene-butadiene copolymer, ethylene-vinyl acetate copolymer, and nitrile-isoprene rubber. [5] The superelastic grinding wheel according to any one of [1] to [4], wherein the degree of acetalization of the partially acetalized product is 5 mol % or more and 50 mol % or less. [6] The superelastic grinding wheel according to any one of [1] to [5], wherein the graft polymer is a copolymer of PVA and polyvinylpyrrolidone, polyethylene glycol, or acrylic acid / methyl methacrylate. [7] The superelastic grinding wheel according to [1] to [6], wherein the abrasive grains contain at least one of alumina, silicon carbide, emery, zirconia, cerium oxide, chromium oxide, silicon oxide, diamond, and cubic boron nitride. Effect of the Invention

[0007] According to one aspect of the present invention, it is possible to provide a superelastic grinding wheel that can achieve improved wear resistance while maintaining conformability to a workpiece. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Preferred embodiments of the present invention will now be described in detail.

[0009] The grinding wheel according to this embodiment is a superelastic grinding wheel, and is used, for example, for final polishing of a workpiece having a polished surface with a complex shape. The superelastic grinding wheel is a grinding wheel that exhibits a nonlinear stress-strain relationship, and enables polishing that conforms to the polished surface even if the polished surface is uneven or curved. Polishing using the superelastic grinding wheel may be manual or automatic. The superelastic grinding wheel includes abrasive grains and a body that holds the abrasive grains.

[0010] (Abrasive grain) The abrasive grains are granular materials that polish the surface to be polished in the grindstone, and are dispersed in and held by the main body. The granular materials are appropriately selected according to the superelastic grindstone to be manufactured. The abrasive grains may include one type of granular material or multiple types of granular materials. The abrasive grains include at least one of natural minerals such as alumina, silicon carbide, and emery, silicon oxides such as zirconia, cerium oxide, chromium oxide, and silica, diamond, and cubic boron nitride. The grain size of the abrasive grains is, for example, #24 to #8000 as defined by JIS R 6001-1:2017. From the viewpoint of exhibiting the superelasticity of the superelastic grindstone well, the grain size of the abrasive grains may be #60 to #2000.

[0011] From the viewpoint of the abrasiveness and superelasticity of the superelastic grindstone, the percentage of abrasive grains in the total mass of the superelastic grindstone (abrasive grain percentage WT%) is, for example, 50% by mass or more and 85% by mass or less, and the percentage of abrasive grains in the total volume of the superelastic grindstone (abrasive grain percentage Vol%) is, for example, 12% by volume or more and 53% by volume or less. The abrasive grain percentage WT% is calculated, for example, from the combustion and specific gravity of the material. The abrasive grain percentage Vol% is calculated, for example, from the cross-sectional area of ​​the superelastic grindstone.

[0012] (Main body) The main body is the part of the grinding wheel that holds the abrasive grains and conforms to the workpiece, and exhibits superelasticity. In this embodiment, the main body is a thermosetting molded body of a binder, which will be described below. The shape of the main body is not particularly limited, but may be, for example, a plate shape or a ring shape. In one example, the superelastic grinding wheel is formed by thermosetting a slurry in which abrasive grains are dispersed in a binder.

[0013] (Binding Agent) The binder is the main material of the body and contains, for example, rubber latex and at least one of a partial acetalization product of PVA (polyvinyl alcohol) and a graft polymer having PVA as the main chain.

[0014] Rubber latex is the main material that exhibits superelasticity in the body. From the viewpoint of the superelasticity of the superelastic grindstone, the content of rubber latex in the binder is 50% by mass or more. From the viewpoint of the wear resistance of the superelastic grindstone, the content of rubber latex in the binder is 80% by mass or less.

[0015] The rubber latex includes at least one of natural rubber latex and synthetic rubber latex. The synthetic rubber latex includes one or more of styrene-butadiene copolymers such as styrene-butadiene rubber (SB rubber), ethylene-vinyl acetate copolymers, isoprene rubber, butadiene rubber, chloroprene, butyl rubber, ethylene propylene rubber, chlorosulfonated polyethylene, nitrile rubber (NBR), acrylic rubber, nitrile-isoprene rubber, epichlorohydrin rubber, urethane rubber, fluororubber, silicone rubber, etc.

[0016] Each of the partially acetalized PVA and the graft polymer having PVA as the main chain is a material contained in the binder to provide continuous pores (details will be described later) in the main body. When the binder contains PVA, which is a linear polymer, a three-dimensional matrix network with the rubber latex is easily formed throughout the main body. When the three-dimensional matrix network is formed in the main body, the wear resistance of the main body is improved. From the viewpoint of compatibility with the rubber latex and the porosity of the main body, the binder contains at least one of the partially acetalized PVA and the graft polymer having PVA as the main chain, rather than simply PVA. From the viewpoint of the wear resistance and superelasticity of the superelastic grinding wheel, the content of the partially acetalized PVA in the binder is 10% by mass or more and 50% by mass or less, and the content of the graft polymer in the binder is 0% by mass or more and 20% by mass or less. Therefore, the binder may contain the partially acetalized PVA while not containing the graft polymer having PVA as the main chain, but is not limited to this. The degree of polymerization of PVA is, for example, 400 or more and 3,500 or less.

[0017] The partially acetalized PVA is a linear polymeric substance in which PVA is partially acetalized with a known aldehyde, and has both an acetyl group and a hydroxyl group in the molecule. The degree of acetalization of the partially acetalized PVA is 5 mol% or more and 50 mol% or less. When the degree of acetalization is 5 mol% or more, a three-dimensional matrix network is well formed between the partially acetalized PVA and the rubber latex. This improves the wear resistance of the main body. In addition, when the degree of acetalization is 50 mol% or less, the compatibility between the partially acetalized PVA and the rubber latex is ensured, so that the abrasive grains are well dispersed in the main body. Examples of the partially acetalized PVA include polyvinyl butyral and polyvinyl formal.

[0018] The graft polymer with PVA as the main chain is a copolymer with PVA as the main chain. The graft polymer is formed by adding a copolymerizable compound at the stage of the polymerization process of PVA. The compound may be a polymer or a monomer. The graft polymer with PVA as the main chain is, for example, a copolymer of PVA and polyvinylpyrrolidone, polyethylene glycol, or acrylic acid / methyl methacrylate, but is not limited thereto.

[0019] The rubber latex contained in the binder is solidified by heating and / or vulcanization by adding a known vulcanizing agent, zinc oxide, sodium silicofluoride, or other coagulating agent. Therefore, the binder may contain additives such as vulcanizing agents and coagulating agents. On the other hand, no catalyst or curing agent is required for the partial acetalization product of PVA or the graft polymer with PVA as the main chain.

[0020] (Interconnected pores) One or more continuous pores are provided in the body by using a binder that is a mixture of rubber latex and at least one of a partially acetalized product of PVA and a graft polymer with PVA as the main chain. The continuous pores are formed when the water generated in the heating and solidification stage, that is, the stage in which the polymer is alloyed, moves to the surface of the grindstone by blending the partially acetalized product and / or the graft polymer with the rubber latex. Therefore, the continuous pores can be said to be pores that connect to the surface of the superelastic grindstone. The water is generated using hydroxyl groups, acetyl groups, and hydroxyl groups of the partially acetalized product and the graft polymer as raw materials.

[0021] From the viewpoint of reducing clogging, the average pore diameter (median diameter) of the continuous pores is, for example, 1 μm or more. By preventing clogging, a mirror surface is continuously obtained on the work surface, so that uneven polishing is less likely to occur. From the viewpoint of wear resistance and polishing performance of the superelastic grindstone, the average pore diameter of the continuous pores is, for example, 10 μm or more in terms of median diameter. In addition, the maximum diameter of the continuous pores is 200 μm or less. From the viewpoint of suppressing wear of the superelastic grindstone, the average pore diameter of the continuous pores may be 40 μm or less, or may be 30 μm or less. From the viewpoint of thermal diffusion performance of the superelastic grindstone, the ratio of the continuous pores in the main body (porosity) is, for example, 10 vol.% or more. From the viewpoint of wear resistance of the grindstone, the porosity is, for example, 40 vol.% or less. The above median diameter and porosity are calculated by mercury intrusion method using "AUTOPORE IV9500" manufactured by Micromeritics.

[0022] (Method of manufacturing superelastic grindstone) Next, an example of a method for manufacturing a superelastic grindstone according to the present embodiment will be described. First, rubber latex, additives, and at least one of a partially acetalized product of PVA and a graft polymer having PVA as a main chain are stirred and mixed. Next, abrasive grains are added and further stirred and mixed to obtain a slurry. After the abrasive grains are added, a dispersant or the like may be further added to generate the slurry. Next, the slurry is poured into a mold, and the mold is placed in a thermostatic bath. This solidifies the slurry to obtain an intermediate body of a superelastic grindstone. Next, the intermediate body is removed from the mold and heat-cured to produce a superelastic grindstone having continuous pores. In the heat-curing, a heat treatment may be performed multiple times.

[0023] The effects of the superelastic grindstone according to the present embodiment described above will now be described with reference to problems associated with the conventional grindstone.

[0024] As mentioned above, when the binder contains rubber latex, the wear resistance of the grindstone tends to be low. When the wear resistance of the grindstone is low, it becomes necessary to change the grindstone in the middle of polishing one workpiece. Changing the grindstone in the middle of polishing one workpiece has the problem of not being able to obtain a stable mirror finish on the workpiece surface. In particular, superelastic grindstones are used for finish polishing. For this reason, if the grindstone is changed in the middle of finish polishing, the gloss state of the product surface will differ from position to position, which will lead to the production of products with defective appearances. In particular, manual polishing tends to produce products with defective appearances. In addition, automatic polishing has the problem of the device becoming complicated because a grindstone changing mechanism is required during polishing.

[0025] In view of the above problems, if fibers or the like are simply added to improve the wear resistance, the superelasticity and porosity of the grinding wheel tend to decrease significantly. In this case, the compatibility of the grinding wheel with the workpiece decreases, and problems such as damage to the workpiece during grinding and a decrease in grinding efficiency may occur. In addition, the decrease in porosity makes clogging more likely to occur. From the viewpoint of suppressing the occurrence of clogging, it is possible to improve the porosity of the grinding wheel. However, simply forming a large number of independent bubbles to improve the porosity makes the shape deformation of the grinding wheel unstable, and the workpiece surface tends to be polished unevenly. In particular, since there is no clear direction during grinding with a superelastic grinding wheel, uneven polishing tends to be performed.

[0026] In contrast, the main body of the superelastic grindstone according to this embodiment is a hardened body of a binder containing rubber latex and at least one of a partially acetalized product of PVA (polyvinyl alcohol) and a graft polymer having PVA as the main chain. As a result, a three-dimensional matrix-like network is formed in the main body by the rubber latex and at least one of the partially acetalized product and the graft polymer. The wear resistance of the main body can be improved. In addition, continuous pores are easily formed in the main body. In addition, at least one continuous pore is provided in the main body, and the porosity of the main body measured by mercury intrusion porosimetry is 10% by volume or more and 40% by volume or less. This improves the heat diffusion performance of the grindstone, thereby reducing the amount of wear of the main body during grinding. Furthermore, the presence of continuous pores maintains the compatibility with the workpiece, which is a feature of the superelastic grindstone. Therefore, by using the superelastic grindstone according to this embodiment, it is possible to improve the wear resistance while maintaining the compatibility with the workpiece.

[0027] In this embodiment, when the main body is measured by mercury intrusion porosimetry, the median diameter of the continuous pores is 1 μm or more and 10 μm or less, and the maximum diameter of the continuous pores is 200 μm or less, which can reduce clogging during polishing with the superelastic grindstone and improve the wear resistance and polishing performance of the superelastic grindstone.

[0028] In this embodiment, the binder may contain 50% by mass or more of rubber latex and 80% by mass or less, 10% by mass or more of partially acetalized product and 0% by mass or more of 20% by mass or less of graft polymer. In this case, the wear resistance and superelasticity of the superelastic grindstone can be set favorably.

[0029] In this embodiment, the degree of acetalization of the partially acetalized PVA is 5 mol% or more and 50 mol% or less. This improves the wear resistance due to the three-dimensional matrix network of the partially acetalized PVA and the rubber latex. In addition, the abrasive grains can be well dispersed in the main body.

[0030] The above embodiment describes one aspect of the present invention, and therefore the present invention is not limited to the above embodiment and may be modified as appropriate. EXAMPLES

[0031] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these examples.

[0032] Example 1 First, 220g of NBR latex ("LX551" manufactured by Zeon Corporation, solid content 45% by mass) was mixed with 5g of vulcanizing agent ("S+MZ" manufactured by Musashino Chemical Co., Ltd.) and 2g of zinc oxide (first-grade reagent) by stirring and mixing for 5 minutes in a homogenizer MARKII (manufactured by Primix Corporation). Next, 120g of polyvinyl butyral with an acetalization degree of 8mol% ("KW-10" manufactured by Sekisui Chemical Co., Ltd., solid content 25% by mass) was added to the mixture and stirred and mixed for another 5 minutes, to which 250g of alumina ("WA800" manufactured by Fujimi Inc., grain size: #800) was added as an abrasive. The mixture of the above mixture, polyvinyl butyral, and abrasive grains was stirred and mixed for 5 minutes, and then 5 g of silicofluoride dispersion ("TNW-16" manufactured by Musashino Chemical Co., Ltd.) was added and stirred and mixed for another minute to obtain a slurry.

[0033] Next, the slurry was poured into a mold, and the mold was placed in a water tank. The temperature in the water tank was set to 50°C, and the mold was left in the water tank for 24 hours. This solidified the slurry, and an intermediate superelastic grindstone was obtained.

[0034] Next, the intermediate was removed from the mold and left in a hot air dryer ("ASSWT OVEN" manufactured by Asahi Scientific Co., Ltd.) set at 90°C for 6 hours. The temperature of the hot air dryer was then set at 135°C, and the intermediate was left standing for 1 hour. This caused the intermediate to harden. The hardened intermediate was then molded into a predetermined shape to manufacture a superelastic grindstone. The bulk density, abrasive grain ratio (mass% and volume%), binder ratio (volume%), porosity, and average pore size of the manufactured superelastic grindstone are shown in Table 1 below. The abrasive grain ratio and binder ratio were calculated from the combustion and specific gravity of the material. The porosity and average pore size were calculated by mercury intrusion method using "AUTOPORE IV9500" manufactured by Micromeritics Co., Ltd.

[0035] Comparative Example 1 289g of NBR latex (Zeon Corporation "LX551", solid content 45% by mass), 5g of vulcanizing agent (Musashino Chemical Co., Ltd. "S+MZ"), and 2g of zinc oxide (reagent grade 1) were stirred and mixed for 5 minutes using a homomixer MARKII (Primix Corporation), and 250g of alumina (Fujimi Incorporated Co., Ltd. "WA800", grain size: #800) was added as abrasive grains. The mixture of the above mixture and the abrasive grains was then stirred and mixed for 5 minutes, after which 5g of silicofluoride dispersion (Musashino Chemical Co., Ltd. "TNW-16") was added and stirred and mixed for another 1 minute to obtain a slurry.

[0036] Next, the slurry was poured into a predetermined mold, and the mold was placed in a water tank. The temperature in the water tank was set to 50°C, and the mold was left in the water tank for 24 hours. This solidified the slurry, and an intermediate rubber grindstone was obtained.

[0037] Next, the intermediate was removed from the mold and vulcanized at 135°C for 1 hour in a water vapor atmosphere. The vulcanized intermediate was molded into a predetermined shape to produce a rubber grindstone. The bulk density, abrasive grain ratio (mass% and volume%), binder ratio (volume%), porosity, and average pore size of the produced rubber grindstone are shown in Table 1 below.

[0038] Comparative Example 2 173g of NBR latex (Zeon Corporation "LX551", solid content 45% by mass), 104g of SB latex (Asahi Kasei Corporation "L-4700", solid content 50% by mass), 5g of vulcanizing agent (Musashino Chemical Corporation "S+MZ"), and 2g of zinc oxide (reagent grade 1) were stirred and mixed for 5 minutes using a homogenizer MARKII (Primix Corporation), to which 15g of pore agent (Potters Ballotini Corporation "Sphericel 25P45") and 250g of alumina (Fujimi Incorporated Corporation "WA800", grain size: #800) were added. The mixture was then stirred and mixed with the abrasive grains for 1 minute to obtain a slurry.

[0039] Next, the slurry was poured into a predetermined mold, and the mold was placed in a water tank. The temperature in the water tank was set to 50°C, and the mold was left in the water tank for 24 hours. This solidified the slurry, and an intermediate rubber grindstone was obtained.

[0040] Next, the intermediate was removed from the mold and vulcanized at 135°C for 1 hour in a water vapor atmosphere. The vulcanized intermediate was molded into a predetermined shape to produce a rubber grindstone. The bulk density, abrasive grain ratio (mass% and volume%), binder ratio (volume%), porosity, and average pore size of the produced rubber grindstone are shown in Table 1 below.

[0041] [Table 1]

[0042] (Polishing test) Each of the grindstones of Example 1 and Comparative Examples 1 and 2 was machined to have a shaft, and the grinding test described below was carried out.

[0043] (Test conditions) Work Dimensions: diameter 54mm, height 73mm, inner diameter 38.5~39.5mm (12-sided coupling part) Material: High carbon chrome bearing SUJ2 hardened (Rockwell hardness: 61) - Shafted grindstone (Shafted grindstone as specified in JIS R 6217:2017) Shape: Cylindrical Dimensions: Outer diameter 15mm, thickness 20mm, shaft diameter 6mm, shaft length 35mm Type: Rubber shaft grindstone (bonding code: R) Minimum usable outer diameter: φ7.5mm Polishing equipment ("Ryuterflex LF-300" manufactured by Nippon Precision Machinery Works Co., Ltd.) Rotation speed: 3000 revolutions per minute (rpm) Pressing angle: 90° Pressing load: 5.9N~7.8N (Imada Co., Ltd. "Force gauge ZTA-50N attached to a grinder" Polishing time: 120 seconds Polishing method: Polish from one 73 mm inner diameter end to 73 mm in the axial direction, then polish from a position shifted by 5 mm in an arc to 73 mm in the axial direction. This is repeated 24 times to complete polishing of one workpiece.

[0044] (Polishing test results) The results of measuring the mass of the workpiece and the shaft-mounted grindstone before and after grinding using the grindstones of the Example, Comparative Example 1, and Comparative Example 2 are shown in Table 2 below. The grinding ratio is the value obtained by dividing the grinding amount (mass) by the grindstone wear amount (mass). It can be said that the larger the grinding ratio, the smaller the grindstone wear amount.

[0045] [Table 2]

[0046] From Table 1 above, the rubber grindstone of Comparative Example 1 has a smaller porosity than the examples, while the bulk density, abrasive grain ratio, and binder ratio are larger. Therefore, as shown in Table 2 above, the grindstone became clogged immediately after grinding and could not be used. In addition, the grindstone of Comparative Example 2 uses hollow glass beads as pores, and did not become clogged. However, there was a lot of wear due to the pore agent, and the axle grindstone had to be replaced twice during grinding of one workpiece, resulting in unevenness in the grinding surface. On the other hand, the superelastic grindstone of the examples has a higher continuous porosity than the rubber grindstones of Comparative Examples 1 and 2. As a result, as shown in Table 2 above, it can be said that the amount of wear is small even in complex internal grinding in the examples, and grinding performance is sufficiently maintained.

Claims

1. Abrasive grains and A body for holding the abrasive grains; Equipped with the main body is a cured product of a binder containing rubber latex and at least one of a partially acetalized product of PVA and a graft polymer having PVA as a main chain, The body is provided with at least one continuous pore; The porosity of the main body is 10% by volume or more and 40% by volume or less when measured by mercury intrusion porosimetry. Super elastic grinding wheel.

2. 2. The superelastic grinding wheel according to claim 1, wherein, when the body is measured by mercury intrusion porosimetry, the median diameter of the continuous pores is 1 μm or more and 10 μm or less, and the maximum diameter of the continuous pores is 200 μm or less.

3. The superelastic grinding wheel according to claim 1 or 2, wherein in the binder, the content of the rubber latex is 50% by mass or more and 80% by mass or less, the content of the partially acetalized product is 10% by mass or more and 50% by mass or less, and the content of the graft polymer is 0% by mass or more and 20% by mass or less.

4. 3. The superelastic grinding wheel according to claim 1, wherein the rubber latex contains at least one of natural rubber, styrene-butadiene copolymer, ethylene-vinyl acetate copolymer, and nitrile-isoprene rubber.

5. 3. The superelastic grinding wheel according to claim 1, wherein the degree of acetalization of the partially acetalized product is from 5 mol % to 50 mol %.

6. 3. The superelastic grinding wheel according to claim 1, wherein the graft polymer is a copolymer of PVA and polyvinylpyrrolidone, polyethylene glycol, or acrylic acid-methyl methacrylate.

7. 3. The superelastic grinding wheel of claim 1 or 2, wherein the abrasive grains include at least one of alumina, silicon carbide, emery, zirconia, cerium oxide, chromium oxide, silicon oxide, diamond, and cubic boron nitride.

Citation Information

Patent Citations

  • Grindstone

    JP2021194723A